PI-RADS 2.1: A Practical Overview - A Dayala Sundaram (Thieme Medical and Scientific Publishers Pvt. Ltd., 2024)
The Prostate Imaging Reporting and Data System (PI-RADS) is an essential tool for standardizing the interpretation of multiparametric magnetic resonance imaging (mp-MRI) of the prostate for detecting prostate cancer. This article provides a comprehensive overview of the latest version, PI-RADS 2.1, with clear pictures to guide radiologists in its practical application for improved diagnostic accuracy. The article explores the key modifications, emphasizing the changes in scoring criteria and their impact on clinical decision-making. It discusses the importance of mp-MRI sequences, such as T2-weighted imaging, diffusion-weighted imaging, and dynamic contrast-enhanced imaging, and clarifies their significance in the PI-RADS 2.1 framework. The article highlights practical insights to help radiologists integrate this updated system into their day-to-day practice, promoting consistency and reliability in reporting.